1981
DOI: 10.1139/f81-228
|View full text |Cite
|
Sign up to set email alerts
|

Variation among Stocks of Walleye (Stizostedion vitreum vitreum): Management Implications

Abstract: NEPSZY. 1981. Variation among stmks of walleye (Stizostedkorz vitreum virrelarat): management implications. Can. J. Fish. Aquat. Sci. 38: 1814-1831.Identification of races, strains, or subpopulations of walleye (StizostecSPorz \'itreurn vitrcwn) by examining differences in the morphology or biochemistry has met with relatively limited success. Although there is some genotypic evidence for stock discreteness, most evidence points to differences (age, growth, fecundity, maturity) which are believed to be phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 9 publications
5
78
0
1
Order By: Relevance
“…The number of strays or migrants per generation required to break down genetic structure can be very small (Waples, 1998); a rate of gene flow as little as 1% can be sufficient to homogenize the gene pool (Carvalho and Hauser, 1994;Waters et al, 2002). Furthermore, although the migratory behavior of walleye has been extensively examined using tagging studies in multiple lake systems (Eschmeyer, 1950;Eschmeyer and Crowe, 1955;Forney, 1963;Foust and Hynes, 2007;Ward et al, 1989), these tagging studies provide no direct evidence that the homing behavior is to an individual's natal site-although it is widely assumed that this is the case (Spangler et al, 1977;Colby and Nepszy, 1981). Olson et al (1978) suggested that homing (or rather site fidelity) in walleye is not a natally-imprinted behavior, but rather learned as an adult.…”
Section: Population Structure Within Lake Winnipeg Walleyementioning
confidence: 99%
See 1 more Smart Citation
“…The number of strays or migrants per generation required to break down genetic structure can be very small (Waples, 1998); a rate of gene flow as little as 1% can be sufficient to homogenize the gene pool (Carvalho and Hauser, 1994;Waters et al, 2002). Furthermore, although the migratory behavior of walleye has been extensively examined using tagging studies in multiple lake systems (Eschmeyer, 1950;Eschmeyer and Crowe, 1955;Forney, 1963;Foust and Hynes, 2007;Ward et al, 1989), these tagging studies provide no direct evidence that the homing behavior is to an individual's natal site-although it is widely assumed that this is the case (Spangler et al, 1977;Colby and Nepszy, 1981). Olson et al (1978) suggested that homing (or rather site fidelity) in walleye is not a natally-imprinted behavior, but rather learned as an adult.…”
Section: Population Structure Within Lake Winnipeg Walleyementioning
confidence: 99%
“…Multiple genetic stocks can co-exist in a single water body if their reproduction is separated either temporally or spatially. Natal homing or spawning site philopatry, a behavior whereby individuals exhibit a tendency to reproduce at the site where they were born, has been extensively documented in walleye by tagging studies in multiple lake systems (Eschmeyer, 1950;Eschmeyer and Crowe, 1955;Forney, 1963;Foust and Hynes, 2007;Ward et al, 1989), but appears to be facultative in some systems (Olson and Scidmore, 1962;Colby and Nepszy, 1981). When present, philopatry results in a spatial separation of spawning aggregations across the lake, providing potential for genetic variation to develop over several generations, and for potentially discrete genetic stocks to form within the lake.…”
Section: Introductionmentioning
confidence: 99%
“…We included lake latitude, season in which each fish was collected, and fish length (cm) in our models to account for possible changes in the spatial distribution of lakes sampled, the seasonal timing of walleye sampling, and the size of walleye targeted for sampling. Lake latitude is also correlated with important gradients in pH and alkalinity, lake productivity, and fish growth (Colby and Nepszy 1981;Lillie and Mason 1983;Lathrop et al 1989;Quist et al 2003;Nate 2004). Fish length is known to be an important determinant of walleye Hg concentrations and must be accounted for in comparing lakes or estimating trends (Wiener et al 1990;Lathrop et al 1991).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Walleye typically undergo a series of ontogenetic diet shifts in their first growing season, moving from zooplankton, to macroinvertebrates and finally to fish (Beck et al, 1998;Fox, 1989;Fox and Flowers, 1990;Fox et al, 1989;Johnston and Mathias, 1994a;Mathias and Li, 1982). The complexity of age-0 walleye food habits during the first growing season allows for many different scenarios in which food could be limiting (Colby and Nepszy, 1981).…”
Section: Introductionmentioning
confidence: 99%